A novel polypeptide encoded by the circular RNA ZKSCAN1 suppresses HCC via degradation of mTOR - Runjie Song; Shuoqian Ma; Jiajia Xu; Xin Ren; Peilan Guo; Huijiao Liu; Peng Li; Fan Yin; Mei Liu; Qiang Wang; Lei Yu; Jiali Liu; et al. (Molecular Cancer, 2023)
Abstract Background hsa_circ_0001727 (circZKSCAN1) has been reported to be a tumor-associated circRNA by sponging microRNAs. Intriguingly, we found that circZKSCAN1 encoded a secretory peptide (circZKSaa) in the liver. The present study aims to elucidate the potential role and molecular mechanism of circZKSaa in the regulation of hepatocellular carcinoma (HCC) progression. Methods The circRNA profiling datasets (RNA-seq data GSE143233 and GSE140202) were reanalyzed and circZKSCAN1 was selected for further study. Mass spectrometry, polysome fractionation assay, dual-luciferase reporter, and a series of experiments showed that circZKSCAN1 encodes circZKSaa. Cell proliferation, apoptosis, and tumorigenesis in nude mice were examined to investigate the functions of circZKSaa. Mechanistically, the relationship between the circZKSaa and mTOR in HCC was verified by immunoprecipitation analyses, mass spectrometry, and immunofluorescence staining analyses. Results Receiver operating characteristic (ROC) analysis demonstrated that the secretory peptide circZKSaa encoded by circZKSCAN1 might be the potential biomarker for HCC tissues. Through a series of experiments, we found that circZKSaa inhibited HCC progression and sensitize HCC cells to sorafenib. Mechanistically, we found that the sponge function of circZKSCAN1 to microRNA is weak in HCC, while overexpression of circZKSaa promoted the interaction of FBXW7 with the mammalian target of rapamycin (mTOR) to promote the ubiquitination of mTOR, thereby inhibiting the PI3K/AKT/mTOR pathway. Furthermore, we found that the high expression of cicZKSCAN1 in sorafenib-treated HCC cells was regulated by QKI-5. Conclusions These results reveal that a novel circZKSCAN1-encoded peptide acts as a tumor suppressor on PI3K/AKT/mTOR pathway, and sensitizes HCC cells to sorafenib via ubiquitination of mTOR. These findings demonstrated that circZKSaa has the potential to serve as a therapeutic target and biomarker for HCC treatment.